2019
DOI: 10.4103/aam.aam_24_18
|View full text |Cite
|
Sign up to set email alerts
|

Epistaxis: The demographics, etiology, management, and predictors of outcome in Jos, North-Central Nigeria

Abstract: Background: Epistaxis, though a mere nuisance can have life-threatening consequences. This first study from Jos on epistaxis aims to determine its sociodemographic characteristics, causes, the treatment modalities and the predictors of patient outcome. Study Design: A retrospective chart review. Methods: Health records of patients that met the inclusion criteria for epistaxis at the Jos University Teaching Hospital, Jos, Nigeria, between Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 11 publications
4
11
2
Order By: Relevance
“…The current study found females to be more affected than males among the study population of 196. This is in contrast with most other studies where the incidence is higher in males [10,20,21]. The male preponderance was attributed to the males being more robust and engaging more in conditions that could predispose to epistaxis, however, this was not the case in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The current study found females to be more affected than males among the study population of 196. This is in contrast with most other studies where the incidence is higher in males [10,20,21]. The male preponderance was attributed to the males being more robust and engaging more in conditions that could predispose to epistaxis, however, this was not the case in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The age group of 30-39 was the most affected followed by age 20-29 years. This was similar to the findings of some other studies in Nigeria; Akinpelu et al and Eziyi et al had 21-40 years as the commonest age affected while Adoga et al also had the 3 rd decade mostly affected in their study [23,24,21]. Also, Gilyoma&Chalya in Northwestern Tanzania, had 31-40 years [25] as the group affected most.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations